2011
DOI: 10.1186/1475-2840-10-76
|View full text |Cite
|
Sign up to set email alerts
|

Plasma osteoprotegerin is related to carotid and peripheral arterial disease, but not to myocardial ischemia in type 2 diabetes mellitus

Abstract: BackgroundCardiovascular disease (CVD) is frequent in type 2 diabetes mellitus patients due to accelerated atherosclerosis. Plasma osteoprotegerin (OPG) has evolved as a biomarker for CVD. We examined the relationship between plasma OPG levels and different CVD manifestations in type 2 diabetes.MethodsType 2 diabetes patients without known CVD referred consecutively to a diabetes clinic for the first time (n = 305, aged: 58.6 ± 11.3 years, diabetes duration: 4.5 ± 5.3 years) were screened for carotid arterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 34 publications
1
28
1
1
Order By: Relevance
“…Several treatments are known to aff ect OPG concentrations, such as insulin, glitazones, and statins [25]. It has also been reported that an increased OPG concentration is associated with carotid and peripheral arterial disease in type 2 DM [20,26]. Our data could, however, not demonstrate the existence of a meaningful linear relationship between any of the ultrasonographic markers of subclinical atherosclerosis and serum OPG level in T2DM subjects.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…Several treatments are known to aff ect OPG concentrations, such as insulin, glitazones, and statins [25]. It has also been reported that an increased OPG concentration is associated with carotid and peripheral arterial disease in type 2 DM [20,26]. Our data could, however, not demonstrate the existence of a meaningful linear relationship between any of the ultrasonographic markers of subclinical atherosclerosis and serum OPG level in T2DM subjects.…”
Section: Discussioncontrasting
confidence: 55%
“…However, sparse data are available on the relationship between plasma OPG levels and markers of subclinical atherosclerosis in subjects with T2DM. Furthermore, increased plasma OPG concentration is associated with carotid and peripheral arterial disease in T2DM [20].…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35] The present study showed the serum OPG levels not to be associated with the severity or extent of coronary atherosclerosis. Interestingly, Poulsen, et al 35) showed that an increased OPG concentration was related to carotid and peripheral artery disease, but not to myocardial ischemia, in patients with type 2 diabetes.…”
Section: Elevated Opg Levels and Coronary Artery Diseases And Cimtmentioning
confidence: 99%
“…In our study, inflammatory cytokines statistically significantly increased CD31+/annexin V+ EMPs to CD62E+ EMPs ratio in T2DM patients. As well known, hs-CRP and OPG appear to be sufficiently increased in T2DM when compared with MetS and may be compensatorily up-regulated in the atherogenic process and in vascular inflammation [42]. In this study we enrolled dysmetabolic patients without angiographic evidences of coronary artery atherosclerosis that allowed us to suggest that the existing vascular inflammation was one of the causal factors contributing to impaired phenotype of EMPs and reflected "vascular competence".…”
Section: Discussionmentioning
confidence: 97%